Deutsches Fest 2015 sebagai Sarana Diplomasi Publik Baru Goethe Institut di Indonesia - Muhammad Faisal Aziz; R.M.T. Nurhasan Affandi; Akim Akim (TRANSBORDERS: International Relations Journal, 2021)
ABSTRACT The new public diplomacy is about building relationships with civil society actors residing abroad and facilitating networking between foreign non-governmental parties. The emergence of new actors in new public diplomacy allows the direct involvement of the public in the diplomatic process. Deutsches Fest is a new practice of public diplomacy. This research aims to see the collaboration between Germany and Indonesia through several projects that are part of the Deutsches Fest with reference to the new theory of public diplomacy. The formulation of the problem in this research is 'what are the characteristics of the new public diplomacy in the implementation of the Deutsches Fest?'. This research explains some of the characteristics of new public diplomacy from the study of international relations found in the implementation of the Deutsches Fest. In examining this problem, researchers use qualitative methods through literature studies and online searches. This research shows that there are several characteristics of new public diplomacy through the implementation of the Deutsches Fest. Not only are there new actors in its implementation, the Goethe Institute is also building a nation brand, new ways of delivering communication, and collaborative relationships with the public in Indonesia. Keywords: New Public Diplomacy, Deutsches Fest, Non-State Actors, New Communication